Role of N–epsilon- carboxy methyl lysine, advanced glycation end products and reactive oxygen species for the development of nonproliferative and proliferative retinopathy in type 2 diabetes mellitus - Choudhuri, Subhadip (Molecular Vision, 2013)
PURPOSE: The aim of the present study was to evaluate the collective role of N-epsilon–carboxy methyl lysine (N(ε)-CML), advanced glycation end-products (AGEs), and reactive oxygen species (ROS) for the development of retinopathy among type 2 diabetic subjects. METHODS: Seventy type 2 diabetic subjects with nonproliferative diabetic retinopathy (NPDR), 105 subjects with proliferative diabetic retinopathy (PDR), and 102 patients with diabetes but without retinopathy (DNR) were enrolled in this study. In addition, 95 normal individuals without diabetes were enrolled as healthy controls in this study. Serum and vitreous N(ε)-CML and AGEs were measured by enzyme-linked immunosorbent assay. The peripheral blood mononuclear cell (PBMC) ROS level was measured by flow cytometric analysis. Serum and PBMC total thiols were measured by spectrophotometry. RESULTS: Serum AGEs and N(ε)-CML levels were significantly elevated in subjects with PDR (p<0.0001) and NPDR (p=0.0297 and p<0.0001, respectively) compared to DNR subjects. Further vitreous AGEs and N(ε)-CML levels were found to be significantly high among PDR subjects compared to the control group (p<0.0001). PBMC ROS production was found to be strikingly high among NPDR (p<0.0001) and PDR (p<0.0001) subjects as compared to the DNR group. Serum and PBMC total thiol levels were remarkably decreased in NPDR (p<0.0001 and p=0.0043, respectively) and PDR (p=0.0108 and p=0.0332 respectively) subjects than those were considered as DNR. CONCLUSIONS: Our findings suggest that N(ε)-CML and ROS are the key modulators for the development of nonproliferative retinopathy among poorly controlled type 2 diabetic subjects. Furthermore, AGEs under persistent oxidative stress and the deprived antioxidant state might instigate the pathogenic process of retinopathy from the nonproliferative to the proliferative state.